Provenance of the Xiashu loess in the lower reaches of the Yangtze River, China: a review - Qian, Peng; Wu, Yunjie; Tian, Zhuang; Yang, Lei; Zheng, Xiangmin; Luo, Jieqiong (Frontiers in Earth Science, 2024)
The Xiashu loess is an important aeolian deposit in eastern China. Research on the provenance of the Xiashu loess, located along the lower reaches of the Yangtze River, has entered into a new stage, compelling us to review the previous research findings in order to provide direction for future research. In this study, we enumerate three different viewpoints regarding the major sources of the loess in eastern China, including distant sources, proximal sources, and mixed sources. We also discuss disturbance factors, methods, and research on the provenance of the Xiashu loess. Previous research has showed that, on the basis of geochronology and meticulous grain grading data, good results as to the loess’ provenance can be obtained using immobile geochemical index tracers that are not affected by chemical weathering or grain size effects. Examples include detrital zircon U-Pb age spectra, major and trace element ratios, stable isotopic composition, and slowly weatherable minerals. However, differences in the data do exist, e.g., for the immobile geochemical provenance tracing indexes of the loess. Also still under debate is the age of the lower boundary of the loess. Therefore, exploring the spatial-temporal variations of the provenance, along with the coupling relationship between the paleoclimate environment evolution and the onset of the loess accumulation, should be comprehensively considered in future research.